Falling through the Cracks: Information Breakdowns in Critical Care Handoff Communication - Abraham, Joanna (American Medical Informatics Association, 2011)
Handoffs have been recognized as a major healthcare challenge primarily due to the breakdowns in communication that occur during transitions in care. Consequently, they are characterized as being “remarkably haphazard”. To investigate the information breakdowns in group handoff communication, we conducted a study at a large academic hospital in Texas. We used multifaceted qualitative methods such as observations, shadowing of care providers and their work activities, audio-recording of handoffs, and care provider interviews to examine the handoff communication workflow, with particular emphasis on investigating the sources of information breakdowns. Using a mixed inductive-deductive analysis approach, we identified two critical sources for information breakdowns - lack of standardization in handoff communication events and unsuccessful completion of pre-turnover coordination activities. We propose strategic solutions that can effectively help mitigate the handoff communication breakdowns.